2019
DOI: 10.1007/978-981-13-6861-5_48
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Student Performance Using Data Mining

Abstract: The series "Advances in Intelligent Systems and Computing" contains publications on theory, applications, and design methods of Intelligent Systems and Intelligent Computing. Virtually all disciplines such as engineering, natural sciences, computer and information science, ICT, economics, business, e-commerce, environment, healthcare, life science are covered. The list of topics spans all the areas of modern intelligent systems and computing such as: computational intelligence, soft computing including neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…The satisfactory accuracy of the algorithm was confirmed, despite the speed of calculation and low consumption of resources. In five cases it was found that Naive Bayes had the highest accuracy (Bergin et al, 2015;Zhou et al 2015;Kamal and Ahuja 2019;Kumar et al 2019;Santoso and Yulia 2019), while the average accuracy of the algorithm reached 0.7560. It should be noted that the required hypothesis of independence between variables cannot be safely assumed or easily manufactured in educational data.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The satisfactory accuracy of the algorithm was confirmed, despite the speed of calculation and low consumption of resources. In five cases it was found that Naive Bayes had the highest accuracy (Bergin et al, 2015;Zhou et al 2015;Kamal and Ahuja 2019;Kumar et al 2019;Santoso and Yulia 2019), while the average accuracy of the algorithm reached 0.7560. It should be noted that the required hypothesis of independence between variables cannot be safely assumed or easily manufactured in educational data.…”
Section: Algorithmsmentioning
confidence: 99%
“…Tang et al: (2015), Klusener and Fortenbacher (2015), Brinton and Chiang (2015), Shrivas and T iwari b. Articles: Al Shehri et al: (2017), Amaya et al: (2015), Widyaningsih et al: (2019) c. Articles: Okubo et al: (2017), Singh and Kaur (2018), Santoso and Yulia (2019), Sumitha et al: (2016), Al Barrak and Al Razgan d. Articles: Amrieh et al: (2015), Ruby and David (2015), Almasri et al: (2019), Sivakumar et al: (2016), Kumar et al: (2019), Chanlekha and Niramitranon (2018) e. Articles: Livieris et al: (2018), Angiani et al: (2019), Jishan et al: (2015), Livieris et al: (2019c), Al Saleem et al: (2015, f. Articles: Kostopoulos et al: (2015), Athani et al: (2017), Sara et al: (2015), Kasthuriarachchi and Liyanage (2019), Namomsa andSharma (2018) g. Articles: Bergin et al: (2015), Navamani and Kannammal (2015), Ketui et al (2019), Bhegade and Shinde (2016), Pristyanto et al, (2018) h. Articles: Lopez Guarin et al: (2015, Pradeep et al: (2015), Yehuala (2015), Kaur and Singh (2016), Mahboob et al: (2017), Pereira et al, (2018)…”
Section: Attributes Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship Mining is the identification of relationships between variables in large data sets [16]. This technique can identify the effective factors on responsible for a student to retake a course [17,18].…”
Section: A Educational Data Mining (Edm)mentioning
confidence: 99%
“…In today's information society, where the amount of data stored is multiplied almost exponentially every day, data mining is a fundamental tool to analyse and exploit it effectively. Data mining techniques provide insight from data relationships and provide researchers and users with rules for classification, association [5]- [7], and prediction. The use of genetic programming in solving classification problems is relatively frequent [8]- [11].…”
Section: Introductionmentioning
confidence: 99%